Global, regional, and national burden of orofacial clefts, 1990–2021: an analysis of data from the global burden of disease study 2021 - Wang, Zhenghao; Qi, Weikun; Chen, Yiru; Niu, Feng (Frontiers in Medicine, 2025)
BackgroundOrofacial clefts (OFCs) are congenital craniofacial malformation caused by embryonic developmental abnormalities, characterized by incomplete fusion of the upper lip and/or palate, leading to feeding difficulties, speech impairments, and other functional challenges. OFCs represent the most prevalent congenital malformations of oral and maxillofacial region. We aim to characterize disease burden of OFCs across regions and countries, analyze temporal trends from 1990 to 2021, examine relationship with Socio-demographic Index (SDI), explore gender disparities and predict future epidemiological patterns.MethodsUtilizing GBD 2021 database for 204 countries/regions, we analyzed age-standardized metrics including disability-adjusted life years (DALYs), prevalence, mortality, incidence, using tools like DisMod-MR 2.1 for Bayesian meta-regression. SDI, calculated from educational attainment, per capita income, and fertility rates (range 0–1), stratified nations into quintiles. Statistical analyses included SDI-burden correlations and future projections using Bayesian age-period-cohort (BAPC) modeling, implemented through R software.ResultsIn 2021, there are a total of 4124006.8 cases of OFCs worldwide, with an age-standardized prevalence rate (ASPR) of 53.4 per 100,000 (95% UI: 43–64). The age-standardized incidence rate (ASIR) was 3.0 per 100,000 (95% UI: 2.2–3.9), while age-standardized deaths rate (ASDR) of 0 per 100,000 (95% UI: 0–0.1). Additionally, age-standardized DALYs rate was 5.8 per 100,000 (95% UI: 3.5–9.8). Regionally, low- to middle-SDI regions demonstrated the highest ASPR and ASIR, whereas low-SDI areas showed the most severe ASDR and DALYs rate. In contrast, high-SDI regions consistently exhibited the lowest burden across all metrics. At the subregional level, South Asia recorded the greatest ASPR, while Central Asia had the peak ASIR. Oceania displayed the highest ASDR and DALYs rate. Country-specific analysis identified Palestine with the maximum ASPR, Kazakhstan with the highest ASIR, Papua New Guinea with the greatest ASDR, and Afghanistan with the most elevated DALYs rate.ConclusionThe global OFCs burden demonstrated consistent decline from 1990–2021, with persistent male predominance. Regional disparities correlate strongly with SDI, particularly affecting Central Asia, South Asia, and Africa populations.